Evolution of non-perfused volume after transurethral ultrasound ablation of prostate: A retrospective 12-month analysis - Mäkelä Pietari; Anttinen Mikael; Wright Cameron; Sainio Teija.; Boström Peter J.; Sequeiros Roberto Blanco (Elsevier Ltd, 2025)
Background
A detailed understanding of the non-perfused volume (NPV) evolution after prostate ablation therapy is lacking. The impact of different diseased prostate tissues on NPV evolution post-ablation is unknown.
Purpose
To characterize the NPV evolution for three treatment groups undergoing heat-based prostate ablation therapy, including benign prostatic hyperplasia (BPH), primary prostate cancer (PCa), and radiorecurrent PCa.
Materials and methods
Study design and data analysis were performed retrospectively. All patients received MRI-guided transurethral ultrasound ablation (TULSA). 21 BPH, 28 radiorecurrent PCa and 40 primary PCa patients were included. Using the T1-weighted contrast-enhanced MR image, the NPV was manually contoured by an experienced radiologist. All patients received an MRI immediately following the ablation. Follow-up included MRI at 3- and 12 months for BPH and radiorecurrent PCa patients and at 6- and 12 months for primary PCa patients.
Results
A significant difference between BPH and radiorecurrent PCa patients was observed at three months (p < 0.0001, Wilcoxon rank sum test), with the median NPV decreasing by 77 % for BPH patients but increasing by 4 % for radiorecurrent PCa patients. At six months, the median NPV decreased by 97 % for primary PCa. Across all groups, although 40 % of patients had residual NPV at 12 months, it tended to be < 1 mL.
Conclusion
The resolution of necrotic tissue after ablation was markedly slower for irradiated than treatment-naïve prostate tissue. These results may account for the increased toxicity observed after radiorecurrent salvage therapy. By 12 months, most necrotic prostate tissue had disappeared in every treatment group.